Factors associated with the number of clinical pharmacy recommendations: findings from an observational study in geriatric inpatients. Issue 2 (4th March 2021) - Van Der Linden, Lorenz; Hias, Julie; Walgraeve, Karolien; Loyens, Silke; Flamaing, Johan; Spriet, Isabel; Tournoy, Jos
ABSTRACT: Objectives : Drug-related problems are prevalent in older inpatients and can be reduced by providing clinical pharmacy (CP) services. Details concerning implementation in clinical practice are frequently lacking. The aim was to describe the output of one such CP program and to identify factors associated with CP recommendations. Methods : A CP program was installed at three acute geriatric wards in a teaching hospital. A convenience sample was collected, consisting of inpatients who received a CP consultation at discharge. Medical conditions, patient demographics, and drug use were evaluated retrospectively. Number and type of the CP recommendations were determined. A Poisson regression analysis was performed to determine factors associated with the number of CP recommendations. Results : A cohort of 524 patients, aged 85 (interquartile range (IQR): 82–89) years was included. On admission, 10.31 (standard deviation: 4.49) drugs were taken. Three (IQR: 2–4) CP recommendations were provided per patient, of which 70.2% targeted drug discontinuation. A model was derived, containing the following factors: number of drugs on admission (incidence rate ratio (IRR): 1.063; 95% confidence interval (CI): 1.052–1.074), number of previous contacts with the geriatric department (IRR: 0.869; 95%CI: 0.816–0.926), presence of left-ventricular dysfunction (IRR: 1.179, 95% CI: 1.023–1.360), the number of new drugs (IRR: 1.046; 95% CI: 1.021–1.071) and use of colecalciferol (IRR: 1.22; 95% CI: 1.088–1.367). Conclusions : Five factors were associated with the number of CP recommendations at discharge. This could allow for further patient stratification to increase the efficiency of the CP program.